Professional performance of natural sciences teachers in terms of school accreditation criteria - Bernawi, Abdul Karim Ben Siddiq; Ali, Amal Mahmoud (Journal of Educational and Psychological Sciences, 2019)
This study aims to identify the differences between means of professional performance criteria and school accreditation variables (academic qualifications- experience years- number of training courses- specialization). It is a complementary part of a thesis entitled “Developing Natural Sciences Teachers’ performance in Medina in terms of school accreditation criteria”. The sample included (171 teachers) from the secondary stage, Medina. It represents (28.12%) of study population. The sample was randomly selected from the governmental daytime schools and the researcher used the surveying descriptive method. The questionnaire included (163 items) distributed into four fields (lesson planning, explaining lessons, evaluating lessons and teacher professionalism), also it includes 19 criteria. To verify instrument reliability and validity, external validity test was performed in addition to perform formative validity (internal constancy). Also, stability test was executed and the total stability was (0.993). To process data, a number of statistical methods used such as; One-Way Anova and Cronbach Alpha. Furthermore, the study introduced a group results whereas the most outstanding are: there is no statistical differences between means of professional performance of teachers and school accreditation criteria in (lesson planning, explaining lessons, evaluating lessons and teacher professionalism) fields and criteria (academic qualification, experience years, training courses and specialization) whereas the significance values were (0.547), (0.089), (0.181) (0.613).